PEMBINAAN DISIPLIN SISWA - Reffy Handriyani; Manap Somantri (Manajer Pendididikan, 2020)
This research described students’ discipline coaching in SMP Negeri 10 Bengkulu City. This research used case study by using qualitative research design. Subjects in this research were students of grade VII, grade VIII, grade IX, Headmaster, vice principal of students, students’ organization coach, Homeroom teacher, subject teachers, and picket teacher. The result of research showed that generally students discipline coaching in SMPN 10 Bengkulu city was appropriate with the rules set by the school, but there still some students who break the rules of discipline in the school. The rule about school discipline consists of rules in learning activities or learning discipline, rules in attitude, rules in students obligations, rules in students presence, and students prohibitions in school environment.